Qualitative exploration of awareness about risk factors and transformative behaviours among Pakistani patients with coronary artery disease - Rubina Barolia; Laila Ladak; Adnan Yaqoob; Aamir Hameed Khan; Furqan Yaqub Pannu (BMJ Open)
Objectives To explore patients’ awareness of risk factors for coronary artery disease (CAD) and experiences of the behavioural modifications, they made during their recovery through in-depth semistructured interviews.Design Qualitative exploration was undertaken as part of a larger project to answer the study questions.Setting Participants were recruited from a public-sector tertiary care hospital in Lahore Pakistan.Participants A total of 20 participants, men and women, who had more than 6 months of experience living with CAD, were recruited using a purposive sampling technique.Results The data were organised and analysed using NVIVO software. An inductive coding approach was used to generate codes, categories and themes. Three themes emerged from participants’ data: lifestyle choices and behavioural factors, reflective awareness and lifestyle changes, holistic perspectives and health management.Conclusions The present study’s findings align with recent literature, emphasising the complex nature of risk factors contributing to heart disease. The participants’ understanding and behavioural changes show the importance of health awareness and preventive measures in reducing cardiovascular risks.